Effects of Magnetic Fields and Metal Ions (Cu, Pb, Al and Fe) on Growth of Anoxygenic Photosynthetic Bacteria (APB) - Sumardi; Farisi, Salman; Agustrina, Rochmah; Yunita (Biospecies, 2019)
Anoxygenic Photosynthetic Bacteria (APB) has beneficial properties including as probiotic candidates, biofertilizers, bioremediation agents, and can reduce H2S concentrations in waters. However, the APB also has a weakness, slow growth.It is known that the interaction of metal ions and the exposure of magnetic fields increases enzyme activity and growth rates. The aim of this study is to determine the effect of metal ions and the exposure to magnetic fields on APB growth. The APB isolate, AM which is isolated from mangrove roots and tested for its effects on metal ions in seawater complete (SWC) media.The metal ions tested were Cu, Pb, Al and Fe with different concentrations. The metal ion is exposed to a 0.2 mT magnetic field for 10 minutes before being added to the media. The cell count results showed that both metal ions exposed and unexposed to magnetic field did not affect the growth of APB AM isolates. However, the metal ion in SWC media affects the spectra pattern of AM APB isolates.